ICSECS-ICoCSIM 2021 - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 23-24 August 2021 - FK, UMP has organised a joint conference of 7th International Conference on Software Engineering & Computer Systems (ICSECS) and 4th International Conference on Computational Science and Information Management (ICoCSIM) 2021.